Elastic scattering of polarized deuterons from H4 between 18 and 22 MeV - Arvieux, J.; Darriulat, P.; Garreta, D.; Papineau, A.; Tarrats, A.; Testono, J. (North Holland Publishing, 1967)
Fil: Arvieux, J. Centre d'Etudes Nuclaires de Saclay; Francia